2019
DOI: 10.14742/ajet.4704
|View full text |Cite
|
Sign up to set email alerts
|

The conceptualisation of cognitive tools in learning and technology: A review

Abstract: The term cognitive tool has been used in many areas of academic specialisation, where it has taken on multiple connotations. In this historical and systematic review, we investigate the conceptualisation of cognitive tools in the learning sciences and educational technology. First, the theory of cognitive tools vis-à-vis learning and development is traced from Vygotsky and Soviet psychology through to its use in current educational technology and learning design. Second, we present a systematic review of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 106 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…Meanwhile, technology usage in learning is closely related to a teacher's belief to provide student-centered learning activities (Sung et al, 2016). Yet, in the student-centered learning theory, a teacher has roles to select tasks, assist student's collaboration, and provide formative feedback ( Pakdaman-Savoji et al, 2019). Thus, we inquired whether the teacher actively provides material, joins the discussion in student's collaboration, conducts assessment, and actively gives feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, technology usage in learning is closely related to a teacher's belief to provide student-centered learning activities (Sung et al, 2016). Yet, in the student-centered learning theory, a teacher has roles to select tasks, assist student's collaboration, and provide formative feedback ( Pakdaman-Savoji et al, 2019). Thus, we inquired whether the teacher actively provides material, joins the discussion in student's collaboration, conducts assessment, and actively gives feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that students with scaffolding of computer SRL tools develop better SRL processes and performance than students without such tools (Manlove et al 2007). In addition, researchers have suggested that tools can be designed to make students' metacognition more explicit and expand their capacity by providing external representation, interactivity, and distributed cognition (Pakdaman-Savoji et al 2019). Therefore, this study proposes SRL tools to assist students in conducting SRL and to externalize their internal SRL processes for observation and measurement.…”
Section: Measurements Of Srlmentioning
confidence: 99%
“…This study designed SRL tools not only to externalize students' internal SRL processes for observation and measurement but also to assist students in SRL by facilitating their SRL processes (parts 3 to 6 in Fig. 2) and by reducing their cognitive load by providing external representation, interactivity, and distributed cognition (Azevedo et al 2010;Lajoie 1993;Pakdaman-Savoji et al 2019;Winne and Nesbit 2009). There are different levels of external feedback, specifically, task, process, self-regulation, and self-level feedback (Hattie and Timperley 2007).…”
Section: Purposes Of This Studymentioning
confidence: 99%
“…At the same time, in the control group, social media were mainly accessed for educational purposes to contact teachers and other students. Based on the experience of the MOOC and other sources [25], most students studying without external control tend to skip exercises and have insufficient motivation to complete the course. Figure 2 shows the use of social media for educational purposes according to the characteristics described above.…”
Section: Resultsmentioning
confidence: 99%